1980
DOI: 10.1111/j.1365-2559.1980.tb02898.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of nuclei and cytoplasm of osteoclasts in Paget's disease of bone

Abstract: To investigate the fine structural features of nuclei and cytoplasm in osteoclasts from patients with Paget's disease of bone, eight bone biopsies were examined. Unusual paracrystalline filamentous formations were found with the nuclei of both actively resorbing and degenerating osteoclasts. These formations were made up of parallel arranged filaments which, in most cases, clustered together regularly. The filaments were slightly argyrophilic and this helped to differentiate them from the surrounding nuclear m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(21 citation statements)
references
References 18 publications
2
19
0
Order By: Relevance
“…In 80 to 9 0~ of these multinucleated cells, hybridization reactions were observed both in the cytoplasm, with a diffuse distribution, and in some of the numerous nuclei, with different levels of intensity. Autoradiographic grains were sometimes concentrated and localized over the nuclear area, in particular over clear nuclear inclusions which very probably correspond to the nuclear accumulation of specific microcytinders as previously described in Pagetic osteoclasts (Gherardi et al, 1980;Harvey et al, 1982;Mills & Singer, 1976;Rebel et al, 1980bRebel et al, , 1974.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…In 80 to 9 0~ of these multinucleated cells, hybridization reactions were observed both in the cytoplasm, with a diffuse distribution, and in some of the numerous nuclei, with different levels of intensity. Autoradiographic grains were sometimes concentrated and localized over the nuclear area, in particular over clear nuclear inclusions which very probably correspond to the nuclear accumulation of specific microcytinders as previously described in Pagetic osteoclasts (Gherardi et al, 1980;Harvey et al, 1982;Mills & Singer, 1976;Rebel et al, 1980bRebel et al, , 1974.…”
Section: Resultssupporting
confidence: 69%
“…Ultrastructural studies have shown the presence of specific inclusions in the enormous, multinucleated osteoclasts from Pagetic bone tissue. Morphological analyses have demonstrated that the structure, the dimensions and the cytoplasmic and nuclear distribution of the microcylindrical inclusions observed in Pagetic osteoclasts are very similar to the nucleocapsids found in cells infected with paramyxoviruses (Gherardi et al, 1980;Harvey et al, 1982;Howatson & Fornasier, 1982;Mills & Singer, 1976;Rebel et al, 1980bRebel et al, , 1974. Furthermore, using immunocytological techniques with polyclonal antibodies, several studies have demonstrated that osteoclasts from bone tissue in Paget's disease contain antigenic material related to measles virus and to respiratory syncytial virus, both of which are members of the family Paramyxoviridae (Basl6 et al, 1979;Mills et al, 1982;Rebel et al, 1980a;Singer & Mills, 1983).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…This conclusion is based on the following observations: (a) Morphologic studies have demonstrated that abnormal osteoclasts are present in pagetic bone (5,6). These osteoclasts are enormous in size (average number of nuclei 20, compared with three to four for normal osteoclasts) and have greatly increased numbers of folds in their cytoplasmic membranes, reflecting their abnormally increased surface activity and motility (7).…”
Section: Introductionmentioning
confidence: 99%
“…Italy, (4) Canada, (5) the United Kingdom, (6,7) Japan, (8)(9)(10) and Czechoslovakia. (11) Osteoclasts in subjects with normal bone did not exhibit the abnormality.…”
Section: Osteoclastsmentioning
confidence: 99%